2019
DOI: 10.1111/aas.13368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pentax Airway Scope and Macintosh laryngoscope for orotracheal intubation in children: A randomised non‐inferiority trial

Abstract: Funding informationDepartmental source. Background: Pentax Airway Scope (AWS) is a recently developed videolaryngoscopefor use in both normal and difficult airways, yet its use in paediatric patients has not been established. The purpose of this study was to evaluate the efficacy of the Pentax AWS regarding intubation time, laryngeal view and ease of intubation in paediatric patients with normal airway, compared to Macintosh laryngoscope.Method: A total of 136 paediatric patients aged 1-10 with American Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Of the 23 included studies, 20 studies 12 – 14 , 30 39 , 41 44 , 46 , 47 , 49 explicitly reported methods for generating random sequence, and 13 studies 13 , 31 , 32 , 34 , 35 , 37 40 , 42 , 43 , 47 , 48 described methods for performing allocation concealment. Most studies 12 – 14 , 30 43 did not blind participants and personnel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 23 included studies, 20 studies 12 – 14 , 30 39 , 41 44 , 46 , 47 , 49 explicitly reported methods for generating random sequence, and 13 studies 13 , 31 , 32 , 34 , 35 , 37 40 , 42 , 43 , 47 , 48 described methods for performing allocation concealment. Most studies 12 – 14 , 30 43 did not blind participants and personnel.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, a total of 16 studies 11 , 13 , 14 , 30 35 , 38 40 , 42 , 43 , 46 , 47 , involving 1288 patients, reported the data of LC for 10 intubation devices. Network meta-analysis suggested that Airtraq significantly reduced the risk of LC compared with Macintosh (OR = 0.14, 95%CI = 0.03 to 0.69) and Pentax (OR = 29.17, 95%CI = 1.93 to 440.66).…”
Section: Resultsmentioning
confidence: 99%
“…A further 202 studies were excluded for the following reasons: non-RCT (n = 56), manikin study (n = 41), case report (n = 33), review or meta-analysis (n = 22), different outcomes (n = 16), use of a flexible fiberscope (n = 11), use of a laryngeal mask (n = 7), observational study design (n = 7), adult patients (n = 4), guidelines (n = 3), and resuscitation research (n = 3). The remaining 34 articles met the inclusion criteria and contained the data necessary for the planned analysis ( Figure S3 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients included in these studies were aged 0 to 10 years. Based on pre-intubation airway assessment, 26 of 34 studies included patients with a normal airway [ 15 , 16 , 17 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 46 , 47 ], and 3 included patients with a difficult airway [ 35 , 36 , 45 ]. Five studies did not provide information on airway status [ 18 , 19 , 21 , 34 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“… • C-MAC® with Macintosh blade A • GlideScope® DVM B Hyper-angulated or hyper-curved blade video laryngoscopy (HA-VL) Hyper-angulated blade VL (HA-VL) allows “around the corner” viewing of the glottis by indirect, videoscopic viewing only. The view with HA-VL is often superior to that obtained by DL 115 117 or Mac-VL. 117 First pass tracheal intubation success with HA-VL is frequently higher than with DL.…”
Section: Response To Difficulty With Airway Management In the Unconscious Patientmentioning
confidence: 86%